Design of Islamic Religious Education Learning Based on Problem-Based Learning - Indriyani Ma’rifah; Ahmad Asroni (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
Islamic Religious Education (IRE) learning in the 21st-century education era is required to develop critical thinking skills, problem-solving abilities, and the strengthening of students’ character. However, in practice, IRE learning is still dominated by conventional, teacher-centered approaches, resulting in learning that tends to be theoretical and less contextual. This article aims to describe the design of Problem-Based Learning (PBL)-based Islamic Religious Education instruction, including its fundamental concepts, implementation stages, learning implications, and strategies for strengthening the PBL design in IRE learning.This study employs a qualitative approach with a library research method. Data were collected from various scientific journals, academic books, and previous studies relevant to Islamic Religious Education and Problem-Based Learning. Data analysis was conducted using content analysis techniques through the stages of data reduction, data display, interpretation, and conclusion drawing. The findings of the study indicate that a PBL-based IRE learning design can create active, contextual, and student-centered learning through the resolution of real-life problems related to theology (aqidah), Islamic ethics (akhlaq), jurisprudence (fiqh), and socio-religious life. The implementation of PBL in IRE learning contributes to improving critical thinking skills, social skills, collaboration abilities, as well as strengthening students’ religious character and religious moderation. In addition, strengthening the PBL design can be achieved through teacher training, integration of digital media, flexible learning time management, and reinforcement of values and character orientation in learning objectives and assessment. Thus, Problem-Based Learning can serve as a strategic alternative in creating IRE that is relevant to the demands of 21st-century education.